SLC46A1 Haplotype with Predicted Functional Impact has Prognostic Value in Breast Carcinoma - Hlavac, Viktor; Vaclavikova, Radka; Brynychova, Veronika; Dvorak, Pavel; Elsnerova, Katerina; Kozevnikovova, Renata; Raus, Karel; Kopeckova, Katerina; Mestakova, Sona; Vrana, David; Gatek, Jiri; Soucek, Pavel (Molecular diagnosis & therapy, 2021)
BACKGROUND AND OBJECTIVE: Membrane solute carrier transporters play an important role in the transport of a wide spectrum of substrates including anticancer drugs and cancer-related physiological substrates. This study aimed to assess the prognostic relevance of gene expression and genetic variability of selected solute carrier transporters in breast cancer. METHODS: Gene expression was determined by quantitative real-time polymerase chain reaction. All SLC46A1 and SLCO1A2 exons and surrounding non-coding sequences in DNA extracted from the blood of patients with breast cancer (exploratory phase) were analyzed by next-generation sequencing technology. Common variants (minor allele frequency ≥ 5%) with in silico-predicted functional relevance were further analyzed in a large cohort of patients with breast cancer (n = 815) and their prognostic and predictive potential was estimated (validation phase). RESULTS: A gene expression and bioinformatics analysis suggested SLC46A1 and SLCO1A2 to play a putative role in the prognosis of patients with breast cancer. In total, 135 genetic variants (20 novel) were identified in both genes in the exploratory phase. Of these variants, 130 were non-coding, three missense, and two synonymous. One common variant in SLCO1A2 and four variants in SLC46A1 were predicted to be pathogenic by in silico programs and subsequently validated. A SLC46A1 haplotype block composed of rs2239911-rs2239910-rs8079943 was significantly associated with ERBB2/HER2 status and disease-free survival of hormonally treated patients. CONCLUSIONS: This study revealed the prognostic value of a SLC46A1 haplotype block for breast cancer that should be further studied.
Keywords: analýza přežití; Sequence Analysis, DNA; Breast Neoplasms; Real-Time Polymerase Chain Reaction; přenašeče organických aniontů; Survival Analysis; Prognosis; regulace genové exprese u nádorů; Proton-Coupled Folate Transporter; Haplotypes; genetická variace; Organic Anion Transporters; Biomarkers, Tumor; Genetic Variation; kvantitativní polymerázová řetězová reakce; folátový přenašeč spřažený s transportem protonů; ženské pohlaví; nádorové biomarkery; prognóza; Humans; Gene Expression Regulation, Neoplastic; High-Throughput Nucleotide Sequencing; haplotypy; vysoce účinné nukleotidové sekvenování; sekvenční analýza DNA; nádory prsu; Female; lidé